Educational psychology - Santrock, John W. ([Place of publication not identifed] : McGraw Hill Education, 2011)
This edition includes fewer boxed features as the material on a number of topics is now integrated seamlessly into the text discussion. Three aspect of educational psychology that appear n the natural flow of the text that previously were separated from the text in boxes are diversity, development and technology .
Educational psychology: a tool for effective teaching -- Cognitive and language development -- Social contexts and socioemotional development -- Individual variations -- Sociocultural diversity -- Learners who are exceptional -- Behavioral and social cognitive approaches -- The information-processing approach -- Complex cognitive processes -- Social constructivist approaches -- Learning and cognition in the content areas -- Planning, instruction, and technology -- Motivation, teaching, and learning -- Managing the classroom -- Standardized tests and teaching -- Classroom assessment and grading.
Includes bibliographical references and index.
Keywords: EDUCATIONAL PSYCHOLOGY